Pengaruh Efikasi Diri, Penghargaan Diri, dan Stress Kerja Terhadap Kinerja Pegawai Puskesmas Muara Teweh Kabupaten Barito Utara - Audia, Lorenza; Sutrisno, Sutrisno; Kadir, Abdul; Abdurrakhman, Zaid (Universitas Hang Tuah, 2021)
The purpose of this study was to determine the effect of self-efficacy, self-esteem, and work stress on the performance of employees of Muara Teweh Community Health Center, North Barito Regency simultaneously, partially, and dominantly. The research method used is an analytical survey. This type of research is explanatory research. The population in this study was 56 people in 2021. The sample in this study used a total sampling technique, namely 56 employees of ASN Puskesmas Muara Teweh, Barito Utara Regency in 2021. Data collection techniques used questionnaires, documentation, interviews, and observations. Validity and reliability tests were carried out on the research instrument. Data were analyzed by multiple linear regression analysis with a classical assumption test. The results showed that self-efficacy, self-esteem, and work stress simultaneously had a significant effect on the performance of the employees of Muara Teweh Community Health Center, North Barito Regency. Self-efficacy, self-esteem, and work stress have a partially significant effect on the performance of employees of the Muara Teweh Community Health Center, North Barito Regency. Self-efficacy has a significant dominant effect on the performance of the employees of the Muara Teweh Community Health Center, North Barito Regency.